Effect of Psychological Stress on Salivary Cortisol and Trace Elements of Copper, Iron and Manganese in Patients with Periodontitis - Ahmed, Nakhshaw Shahab; Hama , Rebwar Gharib; Aziz , Shahram Hama Ali; Azeez, Shokhan Hama Ali (Kurdistan Journal of Applied Research, 2025)
Periodontitis can be described as chronic multifactorial inflammatory disease which can be modified by genetic and environment risk factors such as stress. Trace minerals may impact periodontal tissue health by influencing both locally, the hard and soft tissues, as well as systemically, the immune and inflammatory processes throughout the body. This study aimed to assess salivary levels of cortisol and trace elements between psychologically stressed and non-stressed individuals having healthy periodontium and periodontitis. In this study, eighty adult participants were included. Patients completed a stress self-assessment questionnaire by Perceived stress scale and unstimulated saliva was collected to test cortisol levels by ELISA and trace elements levels of copper (Cu), iron (Fe) and manganese (Mn) by inductively coupled plasma mass spectrometry. The study involved four groups: group 1: non stress with healthy periodontium (NSH), group 2: non stress with periodontitis (NSP), group 3: subjects with stress and healthy periodontium (SH), and group 4: subjects with stress and periodontitis (SP). The result showed that SP group had the highest salivary cortisol level (40.56±4.99), followed by SH (39.75±6.28), NSP (15.22±3.09) and NSH (13.66 ± 3.17) in nmol. Moreover, salivary concentrations of Fe (0.549±0.385mgL−1) and Cu (172±85.447μgL−1) were lowest in SP in comparison with other groups, and Mn (45.032±18.565μgL−1) was significantly reduced in SP group compared to NSP group. It was concluded that the impact of psychological stress on trace elements can result in a significant decrease in all elements in saliva and oral health is greatly influenced by dietary practices and an adequate intake of vital vitamins and minerals.